Enhancing Productivity and Sales through Effective Management of Kits in the Automobile Aftermarket Supply Chain - Vanakudre, Abhijit Ajit (Digital Repository of Theses - SSBM Geneva, 2025)
One of the world's most complicated supply chains is the automotive industry. In order to accurately collaborate, this industry has been found to rely significantly on a large number of outside businesses. In the automobile aftermarket supply chain, efficient kit management is essential for optimizing a number of processes. These are also important for precisely increasing efficiency and are crucial for methodically raising client satisfaction. The research aims to analyse and work to improve total kit productivity to boost revenue and improve effective management. The significance of the study is to drive the effectiveness of productivity and sales through the effective management of kit in the automobile aftermarket supply chain. The main significance of the study is to identify the significant importance of kitting to improve overall business sales and productivity within the automobile aftermarket supply chain process. The study has mentioned that Effective kit management within the automotive aftermarket supply chain is crucial for streamlining multiple operations. In this study, it explored that the automobile market supply chain is serving as one of the critical components in accurately ensuring the availability of the several parts which are necessary for maintenance of vehicles. As industries and technology advance, the kitting and assembly sector is poised for significant transformations. To be competitive and embrace innovations, businesses need to foresee and adapt to these upcoming developments. To be competitive in a rapidly evolving industry, companies must implement and utilize efficient kitting and assembly processes. The preparation of the kits is typically characterised as a labour-intensive operation when it comes to kitting, and reducing operating costs requires time savings. Standardisation and packaging, technological integration, supplier coordination, inventory control, demand forecasting, workforce efficiency, cost considerations, and customer expectations are some of the interconnected factors that affect the dynamics of kit management in the automotive industry. The study includes significant impact of kit management on productivity and sales. In the literature review chapter, it reflects appositive approach towards supply chain by improving the effectiveness of kit management supply chain automatically become successful for automobile industry aftermarket products. Kit management consisting different advantages in supple chain in the areas of cost saving, speed and efficiency, quality and accuracy and also performs in error reduction. Inventory management, quality control and demand forecasting are subjected to be significant challenges that have elaborately identified in the literature review section. They also incorporate the Relationship between supply chain productivity and kit management dynamics within automobile industry. In the literature review chapter, the application of DMAIC application is also mentioned. This framework has been the key source that has accurately facilitated the numerous aspects and provides advantages. Additionally, the chapter also discusses about few methodologies including lean Manufacturing, Stakeholder Theory along with Resources Based View and its applications are also discussed in this study. This research paper researcher is going to conduct a survey process among 101 participants, and the participants were employees/Staff, managers/HR, executives, and customers. These participants have answered the questions that were asked of them during the survey process, and this helps the researcher to depict adequate research findings. On the other hand, researchers have conducted a study by conducting an interview process among 10 people to answer 10 interview questions interview questions. In the phase of qualitative data collection within the study, a total 10 number of participants were selected to participate in a semi-structured interview, and each was guided through 10 interview questions open-ended questions. The usability along with training needs of multiple kit management systems are very significant for accurately ensuring seamless operations and employee efficiency. There are also the requirements or the needs of training for an accurate kit management system. Apart from that, the study has also mentioned that it is essential to provide comprehensive training for different new interfaces of the system and also there is a need to provide training on systems functionality as well as the overall workflows. In addition to that, in this study it has been identified that there are other key areas which are very essential in accurately enhancing the overall effectiveness of the kit management systems by anticipating the requirements of the customer. The primary data analysis findings indicates that the organisations aim to boost sales by implementing different kit management practices, which can also focus on reinforcing these core relational and operational practices. Optimising inventory levels, increasing the dynamic of order fulfilment rates and reducing carrying costs can be achieved through putting in place a strong inventory management system which helps in works with demand projections. Primary data indicates that the automotive aftermarket industry's productivity and sales performance can be further improved through targeted improvements in lead time reduction, supplier and communication and coordination. In addition to that, from the findings of secondary data analysis, it can be known that improvement of the kit productivity that is mainly within the automobile industry in the supply chain process is specifically focusing on accurately streamlining. The secondary data analysis of the study has also highlighted that accurate forecasting is significant for the business performance. It has been the key area that enhances the business performance in determining accurate quantities regarding several components. The respective research paper has critically analyzed how adopting a strategic management of kit can further positively influence entire supply chain performance. The study has developed appropriate findings from the chapter of data analysis through survey and interview process and literature review that a structured approach towards the development of kit configuration, distribution, and inventory control in the conclusion segment. Keywords: Productivity, sales, kits, automobile, aftermarket, supply chain, automotive, inventory, forecasting, warehouse, technology, customer, workforce, efficiency, packaging